An Optimization of Functional Monomer, A Preliminary Study of Meropenem Imprinted Polymer as Selective Sorbent - Lasmaryna Sirumapea; Muhammad Ali Zulfikar; M. Bachri Amran; Anita Alni (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2018)
Molecularly imprinted polymer is a polymer that synthesized together with targeted molecule (analyte) through polymerization process. When the polymerization has completed, extraction is taken to pull the analyte out of the polymer, and it will give a specific “frame” of targeted molecule which leave cavities and further is used to give specific recognition of the analyte. Functional monomer, template molecule, crosslinker agent, porogenic solvent and initiator are the main components involved in the synthesis of this kind of polymer. The right functional monomer is needed to make polymer building block with high selectivity when used as sorbent. The selection of suitable and precise functional monomer has been elaborated in this study. methacrylate acid, itaconic acid and acrylamide is then studies as functional monomer that will be chosen to give the best polymer performance as sorbent. From IR spectrum results, it can be concluded that polymer has been synthesized successfully. Peak at 1157 cm-1 which is a peak of C-N bond from β-lactam ring support this statement. Finally, it can be concluded that methacrylate acid is the best functional monomer for making polymer as sorbent for meropenem